Kepuasan Pelamar Dalam Proses Penerimaan Calon Aparatur Sipil Negara (Casn) Sistem Computer Assisted Test (Cat) Di Lingkungan Pemerintah Kabupaten Lingga - Ahmad Tarmizi Yussa; Rusyidi Darun Rhio (UIR Press, 2020)
This study aims to determine the extent of applicants satisfaction and services quality in the process recruitment civil state apparatus using the CAT system in the district government lingga. Research variables used Reliability, Tangibles, Responsivines, Assurance and Empathy this research is quantitative research, while qualitative research only as supporting data. Population and sample in this research is the applicants pass and do not pass the selection CASN recruitment process. Sampling technique used in determining the individual sample is Cluster Sampling (Area Sampling). The technique of collecting data using questionnaires and interviews. Data analysis technique used is the calculation of Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Based on the calculation CSI obtained a score of 82,45% or at the level very satisfied, on the Cartesian diagram IPA there are two indicators in quadrant I, 7 in quadrant II, 11 in quadrant III and 1 in quadrant IV.